A CASE STUDY ON CULTURE SHOCK BY THAILAND STUDENTS IN PONOROGO - Maimunah Konrasee; Siti Asiyah; Diyah Atiek Mustikawati (Universitas Muhammadiyah Ponorogo, 2020)
This research focuses on culture shock by Thailand students in Ponorogo with two aims: (1) to elaborate on the culture shock by Thailand students in Ponorogo. (2) to investigate the way of Thailand students in Ponorogo adjust their problem with Indonesian culture. This research used qualitative design, while the data were displayed in the forms of descriptive. The researcher took four Thailand students who are studying in Ponorogo. There are one student from Muhammadiyah University of Ponorogo (UMPO), two students from University Darussalam Gontor (UNIDA), and one student from Institute Agama Islam Negeri (IAIN). The researcher used interview and documentation as the instruments for collecting the data. The results showed that there were two problems on culture shock by Thai students in Ponorogo. The problems were: the problems about the cultural difference such as language, social manner, and religious life and the problems about life change such as food, transportation and emotion. Meanwhile, the way to adjust the culture shock in Poronogo by Thai students were: learnt and understand more about host culture, accepted the cultural difference between host culture and their culture, participated in activities related with cultural difference such as summer camp. It helped them to fast adaptation in culture and language, and joined BIPA program (Bahasa Indonesia untuk Penutur Asing). That made them fast adaptation in Indonesia language and also fast adaptation with cultural difference.Keywords: Culture, Thai Culture, Indonesian Culture, Culture Shock